Protein Kinase C-Dependent Effects of Neurosteroids on Synaptic GABAA Receptor Inhibition Require the δ-Subunit - Littlejohn, Erica L.; Boychuk, Carie R. (Frontiers in Physiology, 2021)
The dorsal motor nucleus of the vagus (DMV) contains preganglionic motor neurons important for interpreting sensory input from the periphery, integrating that information, and coding the appropriate parasympathetic (vagal) output to target organs. Despite the critical role of hormonal regulation of vagal motor output, few studies examine the role of neurosteroids in the regulation of the DMV. Of the few examinations, no studies have investigated the role of allopregnanolone (Allo), a neuroactive progesterone-derivative, in the regulation of neurotransmission on the DMV. Since DMV neuronal function is tightly regulated by GABAA receptor activity and Allo is an endogenous GABAA receptor ligand, the present study used in vitro whole cell patch clamp to investigate whether Allo alters GABAergic neurotransmission to DMV neurons. Although Allo did not influence GABAergic neurotransmission during initial application (5-20 minutes), a TTX-insensitive prolongment of decay time and increase in frequency of GABAergic currents was established after Allo was removed from the bath for at least 30 minutes (LtAllo). Inhibition of protein kinase C (PKC) abolished these effects, suggesting that PKC is largely required to mediate Allo-induced inhibition of the DMV. Using mice that lack the δ-subunit of the GABAA receptor, we further confirmed that PKC-dependent activity of LtAllo required this subunit. Allo also potentiated GABAA receptor activity after a repeated application of δ-subunit agonist, suggesting that the presence of Allo encodes stronger δ-subunit-mediated inhibition over time. Using current clamp recording, we demonstrated that LtAllo-induced inhibition is sufficient to decrease action potential firing and excitability within DMV neurons. We conclude that the effects of LtAllo on GABAergic inhibition are dependent on δ-subunit and PKC activation. Taken together, DMV neurons can undergo long lasting Allo-dependent GABAA receptor activity plasticity.